Fecal calprotectin is an early predictor of endoscopic response and histologic remission after the start of vedolizumab in inflammatory bowel disease - Renske W. M. Pauwels; Christien J. van der Woude; Nicole S. Erler; Annemarie C. de Vries (Therapeutic Advances in Gastroenterology, 2020)
Background and aims: Early prediction of the effect of vedolizumab (VDZ) in inflammatory bowel disease (IBD) is of paramount importance to guide clinical decisions. This study assessed whether early fecal calprotectin (FC) can predict endoscopic response and histologic remission after VDZ initiation. Methods: This was a prospective study. Inclusion criteria were endoscopic inflammation and FC >100 µg/g. FC was determined at baseline and weeks 2, 4, 8 and 16. At week 16, endoscopies with ileal and colonic biopsies were performed. FC changes were assessed with Wilcoxon Rank Sum tests. ROC statistics were used to assess the diagnostic accuracy of FC. Results: In total, 45 patients [27 Crohn’s disease (CD), 16/2 ulcerative colitis (UC)/IBD-unclassified] [40% males, median age 39 (28–51) years] were included. Week 16 endoscopic response and histologic remission rates were 58% and 33%. A median 37% decline in FC at week 2 was observed only in endoscopic responders, p  = 0.025. FC <250 µg/g at week 8 predicted endoscopic response in both UC and CD (positive predictive value 100%), whereas absence of FC decline at week 8 corresponded with absence of endoscopic response in CD [negative predictive value (NPV) 82%] and absence of histologic remission in both UC and CD (NPV 90%). Conclusion: The onset of a decline in FC as early as week 2 is associated with endoscopic response to VDZ induction. FC <250 µg/g at week 8 is associated with endoscopic response, whereas absence of FC decline at week 8 is associated with absence of both endoscopic response and histologic remission. FC levels 8 weeks after the start of VDZ could be used to guide clinical decisions and might substitute for endoscopic response evaluation.